Ultrasound-Guided Erector Spinae Plane Block in Thoracolumbar Spinal Surgery: A Systematic Review and Meta-Analysis - Viderman, Dmitriy; Aubakirova, Mina; Umbetzhanov, Yerlan; Kulkaeva, Gulnara; Shalekenov, S. B.; Abdildin, Yerkin G. (Frontiers in Medicine, 2022)
Neurosurgical spinal surgeries such as micro- discectomy and complex fusion surgeries remain the leading causes of disability-adjusted life-year. Major spinal surgeries often result in severe postprocedural pain due to massive dissection of the underlying tissues. While opioids offer effective pain control, they frequently lead to side effects, such as postoperative nausea and vomiting, pruritus, constipation, and respiratory depression. ESPB was successfully used in spinal surgery as a component of a multimodal analgesic regimen and it eliminated the requirements for opioids. The primary purpose of this systematic review and meta-analysis was to compare postoperative opioid consumption between ESPB and placebo. To conduct this systematic review, we used the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)”. We conducted a search for relevant articles available in the following databases: Google Scholar, PubMed, and the Cochrane Library published during the period from the inception to August 2021. Ten articles were included in the systematic review and analyzed. All reported articles were ultrasound-guided.Ultrasound-guided ESPB was superior to placebo in reducing postoperative opioid consumption, pain intensity, postoperative nausea and vomiting, and prolonging the time to first rescue analgesia. There were no ESPB-related serious complications reported.